2011
DOI: 10.2484/rcr.v6i4.545
|View full text |Cite
|
Sign up to set email alerts
|

Spondyloarthropathy occurring in long-standing idiopathic hypoparathyroidism

Abstract: Idiopathic hypoparathyroidism can rarely present with extensive spondyloarthropathic changes that closely resemble ankylosing spondylitis, diffuse idiopathic skeletal hyperostosis, or fluorosis. Clinical presentation of the patient, typical laboratory parameters, and radiological findings aid in their differential diagnosis. Extensive spondyloarthropathy with normal sacroiliac joints in patients with neuromuscular symptoms like tetany, paresthesia, and hypocalcemia should raise the possibility of this entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…4 Image tests that detect the ossification of the ligament iliolumbar are radiography, as our case, CT scan, and MRI. 5 In one case it was detected on bone scintigraphy. 6 In degenerative spondylolisthesis, it is recognized that the sliding of the fourth lumbar vertebra on the fifth vertebra is six times more common when compared to the slide between the fifth lumbar vertebra on the sacrum.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…4 Image tests that detect the ossification of the ligament iliolumbar are radiography, as our case, CT scan, and MRI. 5 In one case it was detected on bone scintigraphy. 6 In degenerative spondylolisthesis, it is recognized that the sliding of the fourth lumbar vertebra on the fifth vertebra is six times more common when compared to the slide between the fifth lumbar vertebra on the sacrum.…”
Section: Discussionmentioning
confidence: 95%
“…The possible causes of ligament iliolumbar calcification or ossification, include: a. Hypoparathyroidism. 5,8 b. Ankylosing spondylitis -seropositive inflammatory spondylarthropathies in general. 7,8 c. Idiopathic skeletal hyperostosis -DISH.…”
Section: Discussionmentioning
confidence: 99%
“…They are accompanied by inflammation at the enthesis sites and mostly HLA-B27 positivity. [1] Due to the differences in the treatment of inflammatory SpA and hypoparathyroidism-associated SpA, a differential diagnosis followed by appropriate treatment is very important. [4] When radiological findings are compared, in SpA, bone density is decreased, syndesmophytes are usually located in the lumbar and lower thoracic region, sacroiliitis is more common and is accompanied by erosion while new bone formation is not usually observed in the acetabulum.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of hypoparathyroidism includes autoimmune, genetic and radiotherapy-related causes and past surgery. [1,2] Hypoparathyroidism is common after thyroid surgery. In a case study with 233 patients, Pelizzo et al [3] reported the rates of transient and permanent hypoparathyroidism following thyroid surgery as 36.4% and 3.3%, respectively.…”
mentioning
confidence: 99%
“…Состояние суставов при гипопаратиреозе характеризуется повышением рисков развития спондилоартропатии, характеризующейся оссификацией связок и образованием синдезмофитов [37]. В небольшой серии клинических наблюдений сообщалось о наличии клинически выраженной спондилоартропатии у 3 из 40 пациентов с гипопаратиреозом, с выявлением радиологических изменений в 14 из 40 случаев [38].…”
Section: скелетно-мышечная система и зубная тканьunclassified